A Multi-Threaded Fingerprint Direct-Access Strategy Using Local-Star-Structure-based Discriminator Features - G. Indrawan; B. Sitohang; S. Akbar; A. S. Nugroho (Institute of Advanced Engineering and Science, 2014)
Taking advantage of multi-thread technology provided by multi-core in single processor, this paper describes multi-thread implementation on fingerprint direct-access strategy using local-star-topology-based discriminator features. Multi-thread was applied for data partitioning on hashing add-lookup process, and for work partitioning on similarity score computation. Efficiency of the implementation was achieved, as confirmed by the results of experiments. Using quad-thread of dual-core single processor on last three largest databases on experiment, multi-thread implementation can reduce searching time at relatively constant value around 300 ms compare to its single-thread implementation. This result achieved with relatively same accuracy trend and has significant improvement by considering millisecond order of searching process on large scale data. DOI : http://dx.doi.org/10.11591/telkomnika.v12i5.5208